Error Estimates of Some Numerical Atomic Orbitals in Molecular Simulations (Communications in Computational Physics, 2018)
Numerical atomic orbitals have been successfully used in molecular simulationsas a basis set, which provides a nature, physical description of the electronicstates and is suitable for $\mathcal{O}$($N$) calculations based on the strictly localized property.This paper presents a numerical analysis for some simplified atomic orbitals, withpolynomial-type and confined Hydrogen-like radial basis functions respectively. Wegive some a priori error estimates to understand why numerical atomic orbitals arecomputationally efficient in electronic structure calculations.